1896 Iowa Acts 104 - (:unkn) unknown (My University, 1896)
Chapter 102-An Act to Revise, Amend, and Codify the Statutes Relative to the Militia, § 22: Prohibited trespassing on encampment grounds. Also prohibited the sale of any malt, spirits, or other intoxicating liquors within one mile of such grounds. Violators guilty of a misdemeanor. The commanding officer of such force may arrest violators.
Keywords: ARMED FORCES